The Relationship Between Socioeconomic Status and Brain Volume in Children and Adolescents With Prenatal Alcohol Exposure - Uban, Kristina A.; Kan, Eric; Wozniak, Jeffrey R.; Mattson, Sarah N.; Coles, Claire D.; Sowell, Elizabeth R. (Frontiers in Human Neuroscience, 2020)
The positive relationship between socioeconomic status (SES) and cognitive performance is mediated, in part, by differences in brain structure in typically developing youth. Associations between brain regions that relate to SES overlap with brain regions known to be sensitive to prenatal alcohol exposure (PAE). Animal models demonstrate that PAE attenuates neural and cognitive benefits of early life enrichment. However, whether or not environmental factors related to SES are associated with brain development in youth affected by PAE remains unknown in humans. Methods. T1-weighted magnetic resonance imaging (MRI) scans were obtained in participants with PAE and compared to age- and sex- matched Controls (n=197, 48% with PAE, 44% girls, 6.5-17.7 years old). General linear modeling was utilized to examine associations between SES and subcortical brain volumes for youth with PAE compared to Controls. Results. Group by SES interactions were observed within the hippocampus (HPC), nucleus accumbens (NAc) and ventral diencephalon (vDC) (corrected p values < 0.05), where positive associations (e.g., higher SES related to larger subcortical volumes) were observed within Controls, but not youth with PAE. Post-hoc analyses examined associations between SES and brain volumes within each group independently, and revealed widespread positive associations among Controls (Amyg, HPC, NAc, Pallidum, Putamen, vDC), but not youth with PAE. Across both groups, larger subcortical volumes were related to higher cognitive performance. Conclusions. Typically developing youth exhibit increased subcortical volumes with increased SES, and surprisingly, this relationship is attenuated, and often absent, in adolescents with PAE. Findings suggest that subcortical brain volumes are neurocognitively relevant in both groups. The present results expand our understanding of the impact of PAE on the developing human brain within varying environmental contexts, and may inform novel environmental interventions that aim to improve, in part, on-going disruptions in brain development among youth with PAE. Our study highlights novel complexities in the pursuit to understand SES-brain associations, as we provide evidence that SES matters for brain outcomes among typically developing youth, and possibly not as much on an already altered brain as a result of PAE.